1876 Wis. Sess. Laws 737, ch. 313, § 3, pt. 59 - (:unkn) unknown (My University, 1876)
Allowed the city to regulate the concealed carry "of any pistol or colt, or slung shot, or cross knuckles, or knuckles of lead, brass or other metal, or bowie knife, dirk knife, or dirk or dagger, or any other dangerous or deadly weapon."
Keywords: CARRY - CONCEALED